Impact of Time and Handwashing on Infection Inference in Scenario‐Based Exposures Among Adults and Children in Japan - Fumikazu Furumi; Yumiko Nishio (Wiley, 2024)
ABSTRACT Introduction The COVID‐19 pandemic has underscored the importance of preventive measures like handwashing and mask‐wearing. However, preschoolers often struggle to comprehend disease transmission. This study examined how time and handwashing impact adults' and preschoolers' inferential processes related to infectious disease transmission. Methods Thirty‐eight Japanese adults aged 18-23 years (8 men; 30 women) and 36 Japanese children aged 5-6 years (15 boys; 21 girls) participated in this study. Participants were presented with scenarios involving an infectious individual who was present (1) at the same time, (2) immediately before, or (3) the previous day. Scenarios were presented via PowerPoint for adults and as a picture‐story for preschoolers, with questions on infection likelihood pre‐ and post‐handwashing. Results Both age groups perceived a significantly higher likelihood of infection for same‐time exposure than for other exposures. Preschoolers estimated a lower likelihood of infection than adults (ηp2 = 0.25). Handwashing significantly reduced perceived infection risk, particularly for same‐time (ηp2 = 0.34) and immediately after (ηp2 = 0.10) exposures. Conclusion This study highlights the critical need for age‐appropriate communication about infection prevention, particularly for young children. Preschoolers exhibited a more positive perception of infectious disease transmission, which necessitates reinforcing multiple preventive measures beyond handwashing. The findings underscore the importance of considering cognitive development and the influence of contemporary experiences like the COVID‐19 pandemic when educating about disease transmission. Future research should further explore the relationship between cognitive development, individual differences, and infection reasoning to enhance public health strategies for varying age groups.